Comparative analysis of persistent pediatric asthma with pulmonary function parameters: a cross-sectional study from South India - Suwethasaravanankrishnan, Suwetha; Devarajan, Aravindan; R., Vidhya Shiva Lakshmi (International Journal of Contemporary Pediatrics, 2026)
Background: Asthma is one of the most common chronic respiratory illnesses in children, causing significant morbidity, absenteeism, and poor quality of life. Despite established guidelines, disparities persist in diagnosis and management, especially in developing regions. Pulmonary function testing remains a crucial tool for assessing airway limitation and disease control, yet its correlation with clinical severity in Indian children is under-reported. Objectives were to compare pulmonary function parameters among children with varying grades of persistent asthma and to examine the association between lung-function indices and disease severity. Methods: This cross-sectional study was conducted in the Institute of Social Paediatrics, Government Stanley Medical College and Hospital, Chennai, from April 2021 to August 2022. One hundred children aged 6-12 years with persistent bronchial asthma were enrolled consecutively. Spirometry was performed according to ATS/ERS 2019 standards using Indian reference equations, and forced vital capacity (FVC), forced expiratory volume in one second (FEV₁), FEV₁/FVC ratio, and peak expiratory flow rate (PEFR) were recorded. Data were analyzed with ANOVA, Chi-square, and Pearson correlation tests. Results: Of 100 children, 38% had mild, 35% moderate, and 27% severe persistent asthma. Mean FEV₁ values declined significantly from 86.2±10.4% in mild to 78.5±11.3% in moderate and 67.8±12.5% in severe asthma (p<0.001). Similar trends were noted for FVC and FEV₁/FVC ratio. A strong negative correlation was observed between asthma severity and FEV₁ (r=-0.61, p<0.001) and FEV₁/FVC (r=-0.57, p<0.001). Poor adherence and exposure to household smoke were associated with lower lung-function scores. Conclusions: Progressive decline in spirometric parameters with increasing asthma severity underscores the value of routine lung-function monitoring in pediatric asthma management. The study re-affirms that FEV₁ and FEV₁/FVC ratios serve as reliable, objective markers for assessing disease control and should complement clinical grading in children with persistent asthma.